Significant reductions in mortality of threatened seabirds in a South African trawl fishery. (29th April 2014) - Maree, B. A.; Wanless, R. M.; Fairweather, T. P.; Sullivan, B. J.; Yates, O.
<x xml:space="preserve">Abstract</x> Read the Commentaries on this Feature Paper: Minimizing seabird by‐catch in industrial fisheries; Challenges in seabird by‐catch mitigation and the Response from the authors: Problems and solutions for seabird bycatch in trawl fisheries